2009
DOI: 10.1016/j.mad.2009.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in microRNA expression in stress-induced cellular senescence

Abstract: Summary We investigated miRNA expression changes associated with stress-induced premature senescence (SIPS) in primary cultures of human diploid fibroblasts (HDF) and human trabecular meshwork (HTM) cells. Twenty-five miRNAs were identified by miRNA microarray analysis and their changes in expression were validated by TaqMan realtime RT-PCR in three independent cell lines of HTM and HDF. SIPS in both HTM and HDF cell types was associated with significant down-regulation of four members of the miR-15 family and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
147
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(161 citation statements)
references
References 75 publications
(62 reference statements)
13
147
0
1
Order By: Relevance
“…However, our findings clearly show that miR-146a is not involved in oxidative stress response in neither younger nor senescent HUVECs. These results are in accordance with previous data showing that robust expression of miR-146a is not associated with growth arrest or stress-induced stasis (Bhaumik et al 2009;Magenta et al 2011;Li et al 2009). We also confirmed that miR-200c and miR-141 were up-regulated in younger and senescent HUVECs in response to oxidative stress (Magenta et al 2011;Li et al 2009).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, our findings clearly show that miR-146a is not involved in oxidative stress response in neither younger nor senescent HUVECs. These results are in accordance with previous data showing that robust expression of miR-146a is not associated with growth arrest or stress-induced stasis (Bhaumik et al 2009;Magenta et al 2011;Li et al 2009). We also confirmed that miR-200c and miR-141 were up-regulated in younger and senescent HUVECs in response to oxidative stress (Magenta et al 2011;Li et al 2009).…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, there was an almost 2-fold increase in up-regulated miRs compared to down-regulated ones in senescent cells. This finding is in accordance with data reported regarding in vitro cultured cells and tissues of aged animals and humans, suggesting that an over-expression of miRs might counteract the age-related increase in the expression of protein-encoding genes (Maes et al 2009;Bates et al 2010;Li et al 2009). Among the 367 profiled miRs, miR-146a, miR-9, miR-204 and miR-367 were significantly up-regulated in senescent vs. young cells with miR-146a showing the highest expression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…32 Finally, we focused on the mechanism of miR-200c induction by H 2 O 2 . We found that, miR The results of the present work and of previous studies indicate that in EC, H 2 O 2 causes pRb dephosphorylation by different mechanisms: PP2A activity, p53 and p21 increase, and also by a miR-200c-dependent mechanism involving a ZEB1-mediated upregulation of p21.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently found that, although miR-183 is normally expressed only at low levels in human trabecular meshwork (HTM) cells and human diploid fibroblasts (HDF), its expression increased significantly after the induction of cellular senescence by exposure to H 2 O 2 in these two different cell types (7). Because cellular senescence is recognized as an anticancer mechanism (8), this observation has led us to hypothesize that miR-183 could play a role in the phenotypic changes characteristic of senescent cells, and, in particular, those involved in preventing malignant transformation of aging cells.…”
Section: Mir-183mentioning
confidence: 99%